Pathological Study of Reproductive Tracts of Awassi Ewes in Fallujah, Iraq - Ahmed Sami Jarad1 , Abdul Sattar Faraj Majeed2 , Qusay Mohammed Aboud2 , Mustafa Salah Hasan3, Walee (Indian Journal of Forensic Medicine & Toxicology, 2021)
A total of forty female genital tracts of local sheep, collected from Al-Fallujah abattoir, were utilized forthis study during the period from October 2018 to March 2019. Among these 20% of the samples werepregnant with out any abnormality, and 80% were non pregnant (55% without any problem and 25%showed abnormal macroscopically lesion. The main type of abnormalities were, ovarian adhesion, uterusunicornis, inactive ovaries, cystic ovaries, ovarian germ cell tumor and cervical tumor, metritis, salpingitisand hydrosalpinx with an incidence of 10%, 10% , 10%, 20%, 10% , 10% , 10% , 10% and 10% respectively.The histopathological study revealed that there were a histopathological changes in the previous cases, theovarian giant cell tumor reported at first in this study in Iraq